BIODEGRADABILITY OF BIOPLASTIC IN NATURAL ENVIRONMENT - Rahman, Anggun Rahman; Syamsu, Khaswar Syamsu; Isroi, Isroi Isroi (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2019)
Biodegradation of the bioplastic composite based on cellulose from oil palm empty fruit bunches was investigated in this study. Microbes consortium from landfill soil collected from top soil were used as the inoculums for the biodegradation process. Biodegradation test of the bioplastic from oil palm empty fruit bunch samples compared with oxodegradation and conventional plastic samples were conducted in the glass jar. The biodegradation rate was evaluated from CO2 generated from the biodegradation process and absorbed by 0.1 N sodium hydroxide solutions. The generated CO2 was titrated with 0.1 N HCl and using phenolphthalein (PP) followed by methyl oranges indicator. The results showed that the highest CO2 production on landfill soil indicating the highest rate of biodegradation was found on bioplastic from oil palm empty fruit bunch followed by oxodegradable plastic and conventional plastic. The rate of biodegradation for bioplastic from oil palm empty fruit bunch, oxodegradable plastic and conventional plastic were 0.067mg CO2/day, 0.052 mg CO2/day and 0 mg CO2/day, respectively.